Pengaruh Permainan Tradisional terhadap Regulasi Emosi Anak Usia Dini - Yulita Sandra Muliati (Institut Agama Islam Riyadhlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2026)
This study is motivated by the critical role of emotional regulation in early childhood development, which requires appropriate and sustained stimulation. The purpose of this study is to determine the effect of traditional games on emotional regulation in early childhood. A quantitative approach with a quasi-experimental design (one group pretest-posttest) was employed. The subjects were 20 children aged 5–6 years at KB Bintang Kejora Poco, selected purposively. Data were collected through observation using a rating scale covering four emotional regulation indicators. The intervention lasted four weeks through traditional game activities including engklek, ular naga, and tarik tambang. Results showed improvement in mean scores from 62.50 (moderate category) to 81.75 (good category). The paired sample t-test revealed a significance value of p = 0.000 (p < 0.05), confirming that traditional games significantly affect emotional regulation in early childhood. This study benefits PAUD teachers in selecting culturally-based learning strategies. The novelty lies in the specific focus on emotional regulation as the dependent variable within the context of local traditional games.